Inovation Of Tatungkuik Coffee With Cocholate Flavor Variant - Andri Satrio Saputra; Lise Asnur (Universitas Negeri Padang, 2025)
This study aims to develop an innovative variant of Tatungkuik coffee by adding chocolate flavor, responding to consumer trends that favor unique combinations of traditional and modern tastes. The research used a single-factor experimental design with two formulations tested through organoleptic evaluation using a 5-point Likert scale, assessing color, aroma, taste, and overall quality. Three trained panelists, all experienced coffee consumers with normal sensory abilities, conducted the evaluation. Sample 1 showed the highest preference with a mean overall score of 4,67 out of 5 (91,75%), while Sample 2 had a mean overall score of 3,75 out of 5 (68,75%). This indicates that the chocolate variant significantly enhances the appeal and market potential of Tatungkuik coffee.